The Problem of Universal Education - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 1998)
During the 20th century educology depended upon various unilateral philosophical and ideological trends: positivism, pragmatism, existentialism, Marxism etc. This fact made negative influence on integrity educational science and conditioning of public education. In this situation origination of the universal educology and universal educational system is required. The problem of universal education has some complex aspects: universality, all-roundness, community, usability. In Lithuania prof. Stasys Šalkauskis began to examine this problem already in the first half of the 20th century. Now, as European nations try for unification, more possibilities appear for the cooperation of development of integral universal educational science and system.
Keywords: philosophy of education; educational system; S. Šalkauskis; universal education